Pengaruh Perubahan Pola Ruang Terhadap Tingkat Resapan Air - Studi Kasus di Kecamatan Arjawinangun Kabupaten Cirebon - Achmad Firmansam Bastaman; Putra Arta Samodro (University of Insan Cendekia Mandiri, 2021)
The development of the city is very fast. Various socio-economic activities grow in line with the development of various human needs. The need for land to accommodate these various activities is difficult to avoid, so the city seems to be competing to build and consume the existing land. This condition has an impact on decreasing water absorption, thus threatening various disasters such as floods, the destruction of biodiversity, and drought, of course, the scarcity of clean water. Facing this phenomenon, the research examines the extent to which land use changes affect the level of water infiltration by calculating changes in the conservation index. This study takes the case in Arjawinangun Sub District. The selection of this location is solely due to the availability of data and the spatial plan that is currently being prepared whether it can become one of the parameters for changes in land use in the future.